Molecular Level Analysis Reveals Changes in Chemical Composition of Dissolved Organic Matter From South Texas Rivers After High Flow Events - Lu, Kaijun; Liu, Zhanfei (Frontiers in Marine Science, 2019)
Riverine dissolved organic matter (DOM) is a major source of reduced carbon exported from land to marine environments, and the inflow of riverine organic matter greatly affects biogeochemical cycling in estuaries and bays. Thus, any change in DOM composition, such as changes caused by flood waters as a result of storms and hurricanes, can subsequently affect estuarine environments. To investigate the impact of high flow events on riverine DOM, multidimensional molecular level information of DOM from four south Texas Rivers (Aransas, Lavaca, Mission, and Nueces Rivers) was acquired using high-resolution Ion Mobility Quadrupole Time of Flight Liquid Chromatography Mass Spectrometry (IM Q-TOF LCMS). Base-flow samples were collected in May, July and October of 2016, June of 2017, and March of 2018, while high-flow samples were collected in September of 2017, and June and September of 2018. Based on the molecular formula assigned from IM Q-TOF LCMS, H/C ratio decreased during high-flow event (1.52 to 1.51 in ESI+; 1.19 to 1.07 in ESI-), while O/C ratio increased (0.31 to 0.33 in ESI-). Furthermore, DOM shifted from a protein-like and lipid-like dominated community at base flow condition, to a lignin, tannin and condensed aromatic structure dominated one during high flow event based on MS and tandem MS data. These changes in high-flow riverine DOM indicate an increase of terrestrial signal, which likely is a result of mobilization of terrestrial organic matter from the watersheds by flooding. These mobilized DOM, though refractory at high-flow condition in rivers, could be reactive in coastal regions when condition changes, and thus potentially fuel microbial activities downstream. In addition, about 3.76 – 21.8% of DOM molecules contain structural isomers among different flow conditions. This low number of isomer percentages suggests that as the products of various enzymatic biochemical reactions, the number of isomers in DOM is constrained. Taken together, our study provides insights into structural changes of riverine DOM in response to extreme climate events in subtropical regions and have implications in understanding biogeochemical changes in estuaries under a changing climate.